2016
DOI: 10.5812/cardiovascmed.29291
|View full text |Cite
|
Sign up to set email alerts
|

Those who perceive their disease as a physiological or psychological risk factor experience more anxiety at the beginning of the cardiac rehabilitation program

Abstract: Background:In a cardiac patient, anxiety is the result of the individual’s perception of the treatment and is characterized by inability to predict, control, or achieve the desired treatment outcomes.Objectives:This study was carried out to investigate the extent of clinical anxiety in patients who underwent a cardiac rehabilitation program with different attitudes toward the disease risk factors.Patients and Methods:The administrative data of this retrospective study were obtained from the database of the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…This 20-item scale has three subscales, which are concern for risk (items 1, 2, 4, 5, 7, 8, 9), risk (3,11,12,14,15,16), and unawareness of risk (6,10,17,18,19,20). The scoring is based on the Likert scale (totally disagree = 1 to totally agree = 4).…”
Section: Perception Of Risk Of Heart Disease Scalementioning
confidence: 99%
See 1 more Smart Citation
“…This 20-item scale has three subscales, which are concern for risk (items 1, 2, 4, 5, 7, 8, 9), risk (3,11,12,14,15,16), and unawareness of risk (6,10,17,18,19,20). The scoring is based on the Likert scale (totally disagree = 1 to totally agree = 4).…”
Section: Perception Of Risk Of Heart Disease Scalementioning
confidence: 99%
“…Clearly, more than anything else, behaviors are affected by the thoughts, beliefs, and attitudes of individuals (13). The attitudes of patients with CVDs regarding the diseases risk factors play a central role in mental and physical health and healthy behaviors (14)(15)(16). The attitudes directly affect the health behavior of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] However, the mismatch between actual and perceived risk factors may affect the patient's cognitions[ 12 ] and lead to increased anxiety. [ 13 14 ] Patients’ beliefs about the cause of cardiac disease (perceived risk factors) are part of the global psychological presentation of disease which is affected by patients’ health literacy. [ 7 ] It has been suggested that wrong thoughts about cardiac disease and its risk factors can increase the probability of negative outcomes and of further hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…The tensions during awaking time and occupational and social challenges through decreasing positive mood can lead to distressing sleep and annoying dreams (2,8). For example, patients with cardiovascular problems usually experience high psychological distress because of death risk and invasive treatment procedures (9). Cardiac disease is concerned as a trigger to occur anxiety and depression or related disorders such as post-traumatic stress disorder (PTSD) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%